ANALISIS SHOPEE PAYLATER DAN SHOPEE GAME TERHADAP KEPUTUSAN PEMBELIAN PADA E-COMMERCE SHOPEE PADA PENGGUNA APLIKASI SHOPEE MAHASISWA UNIVERSITAS NUSANTARA PGRI KEDIRI - Amelia, Sella (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This research is motivated by the phenomenon of the spread of the internet which is the impact of the development of information technology infrastructure. Business processes carried out through the media of information technology and the internet are known as e-commerce. E-commerce is a business that uses virtual space as a place to carry out its operations. The purpose of this study was to analyze the shopee paylater and shopee game on purchasing decisions on e-commerce shopee on shopee application users, students of Nusantara University PGRI Kediri. This research uses a quantitative approach. The sample used in this study was 88 people using the slovin formula. The results of this study indicate: (1) Shopee paylater partially influences purchasing decisions on e-commerce on shopee application users, Universitas Nusantara PGRI Kediri. (2) Partially, the shopee game has an effect on purchasing decisions on e-commerce for shopee application users, Universitas Nusantara PGRI Kediri. (3) Simultaneously, there is an effect of shopee paylater and shopee game analysis on purchasing decisions on e-commerce for shopee application users for Universitas Nusantara PGRI Kediri students.